Expression variation and covariation impair analog and enable binary signaling control - Kyle M Kovary; Brooks Taylor; Michael L Zhao; Mary N Teruel (Molecular Systems Biology)
Abstract Due to noise in the synthesis and degradation of proteins, the concentrations of individual vertebrate signaling proteins were estimated to vary with a coefficient of variation (CV) of approximately 25% between cells. Such high variation is beneficial for population‐level regulation of cell functions but abolishes accurate single‐cell signal transmission. Here, we measure cell‐to‐cell variability of relative protein abundance using quantitative proteomics of individual Xenopus laevis eggs and cultured human cells and show that variation is typically much lower, in the range of 5–15%, compatible with accurate single‐cell transmission. Focusing on bimodal ERK signaling, we show that variation and covariation in MEK and ERK expression improves controllability of the percentage of activated cells, demonstrating how variation and covariation in expression enables population‐level control of binary cell‐fate decisions. Together, our study argues for a control principle whereby low expression variation enables accurate control of analog single‐cell signaling, while increased variation, covariation, and numbers of pathway components are required to widen the stimulus range over which external inputs regulate binary cell activation to enable precise control of the fraction of activated cells in a population.